2019
DOI: 10.1002/ejoc.201900356
|View full text |Cite
|
Sign up to set email alerts
|

A General Photocatalytic Route to Prenylation

Abstract: Prenylation is an essential reaction on which nature relies to modify properties of molecules and build terpenoids, but remains a challenging chemical reaction. Aiming to capitalize on recent advances in photocatalysis to easily and cleanly generate a broad range of carbon based radicals, we have developed a prenyl transfer reagent that is captured by transiently generated radicals. The reagent can be made in bulk, is bench stable, and broadly applicable such that it can be used with existing photocatalytic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“… 71 This same catalytic system was utilized in 2020 by Weaver and co-workers for the prenylation of thiophenol using a sulfone reagent, affording the corresponding sulfide in 91% yield. 592 After thiyl radical generation and addition across the olefin moiety as in the above manner, elimination of phenylsulfonyl radical affords the product. Reduction of this radical by EY •– returns the ground-state photocatalyst with phenylsulfinate anion as a byproduct.…”
Section: S -Centered Radical Generation From S–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
See 3 more Smart Citations
“… 71 This same catalytic system was utilized in 2020 by Weaver and co-workers for the prenylation of thiophenol using a sulfone reagent, affording the corresponding sulfide in 91% yield. 592 After thiyl radical generation and addition across the olefin moiety as in the above manner, elimination of phenylsulfonyl radical affords the product. Reduction of this radical by EY •– returns the ground-state photocatalyst with phenylsulfinate anion as a byproduct.…”
Section: S -Centered Radical Generation From S–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…Weaver and co-workers later expanded this methodology to include azole C2-arylation in the presence of electron-rich arenes, 1025 and azole C2-prenylation in the presence of a prenyl sulfone reagent. 592 …”
Section: Reductive Transformations Of Heteroarenes Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…It could also serve a more abstruse role, such as preventing the formation of light absorbing compounds that could lead to photostarvation (Figure 1). 48 The screening for the identity of the terminal reductants revealed that tributylamine and diisopropylethylamine (Table 2, entries 14−16 and the Supporting Information) were nearly identical, while all the other reductants attempted gave poor yields of or no product. We chose to utilize DIPEA due to its comparatively higher vapor pressure and water solubility, which we anticipated would facilitate product isolation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%